Kushite Princess Amun Rhodes I, "Holy Wife of Amun", Ruler of Upper Egypt (The International Journal for Scientific Research, 2023)
Political conditions in Egypt during the period of the New Egyptian Kingdom (1575-1084 B.C) helped to control to the priesthood of Amoun on religious and political issues, especially in southern Egypt. It elevated the position of the Divine Adoratrix, the wife of Amoun, particularly in the Kushite period in the fifteenth dynasty when Kushite Princesses controlled governing issues in South Egypt on behalf of their brothers, the kings. The Kushite princess Amoun Ridis was the first Divine Adoratrix to take on this important position.
Keywords: New Egyptian Kingdom; Twenty-Fifth Dynasty; Kush; Divine Adoratrix; God’s Wife of Amun